Foreign Direct Investment (FDI ) and Protecting Bangladeshi Worker's Human Rights - Mohammad Belayet Hossain (Research Horizon, 2022)
It is the constitutional rights for every citizen to enjoy fundamental human rights. Despite ILO conventions, host countries like Bangladesh have failed to protect workers' human rights. In the name of business, the human rights of workers have been violated significantly in the poor host states. There are ample evidences, which show that their human rights were neglected by Multinational Enterprises (MNEs) or even by the host government. The objective of this study is to examine all the national laws and policies, FDI legislation, and BITs of Bangladesh that apply to labors to assess their adequacy, strength, weaknesses, and gaps in protecting the human rights of workers.